The impact of multisensory learning model-based tale-telling on listening skills and student opinions about it - Gazioğlu, Mustafa; Karakuş, Neslihan (Frontiers in Education, 2023)
This study aims to reveal the impact of multisensory learning model-based taletelling on listening skills. The ‎research has been carried out under hybrid research design using both quantitative and qualitative research ‎methods together. The study group of the research consists of 13 5th-grade students in total who were studying in ‎a public school during 2020 to 2021 academic year. Students have been involved in the research voluntarily ‎and with parental permissions. The following data collection tools have been used in the research: "Attitude ‎Scale Towards Improving Listening Skills with Tales", which was created by the researcher, tale diaries, and tale ‎self-evaluation forms. Quantitative and qualitative data analysis methods have been used to analyse the ‎research data. T-test analysis has been applied on the quantitative data after transferring them to the SPSS data ‎analysis program; on the other hand, content analysis has been used to analyse the qualitative data. As a result ‎of the research, it has been concluded that the multisensory learning method-based taletelling has a positive ‎impact on the attitudes of the 5th-grade students towards tale listening. In the light of the results, it has been ‎concluded that parents have been satisfied with the activities for multisensory taletelling, students have ‎understood the plots of the tales correctly, themes have been remembered correctly by the students most of the ‎time, and parents have shown a positive attitude towards tale listening.‎ Key Words: Tale, Listening Skills, Multisensory Learning, Attitude